2017
DOI: 10.1038/s41598-017-00690-y
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Tissue Engineering by the 3D Bioprinting of iPS Cells in a Nanocellulose/Alginate Bioink

Abstract: Cartilage lesions can progress into secondary osteoarthritis and cause severe clinical problems in numerous patients. As a prospective treatment of such lesions, human-derived induced pluripotent stem cells (iPSCs) were shown to be 3D bioprinted into cartilage mimics using a nanofibrillated cellulose (NFC) composite bioink when co-printed with irradiated human chondrocytes. Two bioinks were investigated: NFC with alginate (NFC/A) or hyaluronic acid (NFC/HA). Low proliferation and phenotypic changes away from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
336
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 378 publications
(343 citation statements)
references
References 35 publications
2
336
2
3
Order By: Relevance
“…Gel‐like materials are readily printed using pressure‐driven printers, also known as bioprinters. Alginate and CNF mixtures have already been demonstrated as being suitable for 3D printing, as the ratio of alginate to CNF and the ionic strength give a precise control over the viscosity of the gel, making it possible to print thin and stable gel layers. As shown in Figure , a 3D‐printing step can be implemented in the aerogel preparation route.…”
Section: Aerogels From Cellulose Nanofibers and Sodium Alginatementioning
confidence: 99%
“…Gel‐like materials are readily printed using pressure‐driven printers, also known as bioprinters. Alginate and CNF mixtures have already been demonstrated as being suitable for 3D printing, as the ratio of alginate to CNF and the ionic strength give a precise control over the viscosity of the gel, making it possible to print thin and stable gel layers. As shown in Figure , a 3D‐printing step can be implemented in the aerogel preparation route.…”
Section: Aerogels From Cellulose Nanofibers and Sodium Alginatementioning
confidence: 99%
“…Nguyen et al bioprinted iPSCs combined with irradiated chondrocytes and hyaline cartilage tissue which formed hyaline like cartilage with type II collagen expression (Fig. A) . Recently, another group compared three different bioinks loaded with BMSCs (a) GelMA, (b) GelMA + chondroitin sulfate aminoethyl methacrylate (CS‐AEMA), and (c) GelMA + CS‐AEMA + hyaluronic acid methacrylate .…”
Section: Bioprinted Tissuesmentioning
confidence: 99%
“… Bioprinted tissues. (A) : 3D‐bioprinted chondrocyte‐derived iPSCs at week 5 of differentiation, sections stained for GAGs, Safranin O for cartilage (with nuclear counterstain), and H&E for extracellular matrix (with nuclear counterstain) (the scale bar represents 100 μm or 500 μm) (Reproduced with permission from ). (B) : Micro‐CT images of polylactic acid/hydroxyapatite scaffold (left) versus bone defect without scaffold (right) after 4 weeks in vivo.…”
Section: Bioprinted Tissuesmentioning
confidence: 99%
“…In addition, they have shown that the encapsulated stem cells can be differentiated into osteoblasts and chondrocytes, further developing the tissue as a tracheal cartilage ring. Similarly, Nguyen et al printed human iPSCs into cartilage using a nanofibrillated cellulose (NFC) composite bioink together with irradiated human chondrocytes. These bio‐printed tissues are paving the path for novel treatments to repair damaged cartilage.…”
Section: Bio‐printing Stem Cellsmentioning
confidence: 99%